Electrolytic effects on the rheology of graphene oxide dispersions. Issue 2 (3rd April 2017) - Shu, Ruiwen; Gan, Ying; Tan, Dexin
ABSTRACT: As graphene oxide (GO) and GO-based composites are generally processed from aqueous dispersion, the rheology is significant for their application. Herein, the effect of inorganic electrolyte (NaCl) concentration on the rheology of GO dispersions containing poly(ethylene glycol) (PEG) was investigated. Small amplitude oscillatory frequency sweep results demonstrated that the linear storage modulus G' enhanced with increasing NaCl concentration. An apparent strain overshoot was observed from the loss modulus G″ under large strain amplitude. Moreover, the aqueous GO/PEG dispersions both presented a local minimum of linear storage modulus G' whether the NaCl was added or not. Significantly, a characteristic shear-thickening was found in aqueous GO/NaCl dispersions regardless of the PEG concentration. Therefore, the study of the rheology of GO in aqueous electrolyte dispersions could contribute to understand the dynamically structural evolution of a class of two-dimensional anisotropic colloid sheets with large aspect ratio and also maybe expand the application of GO dispersions.